Encyclopedia of science (New York DK Multimedia, 1996)
An Encyclopedia of science with over 40 video sequences, 80 animations, 3.5 hours of audio, 800 full-color photos and illustrations, and more than 900,000 words of text.
Title from disc label.
Production level cataloging.
System requirements for Macintosh: Macintosh 68LC040 25MHz PC; System 7.0.
System requirements for Windows: 486DX/25MHz PC; Windows 95 3.1.
Keywords: Science -- Encyclopedias -- Software